Contribution of Agroforestry Biomass Valorisation to Energy and Environmental Sustainability - David Muñoz-Rodríguez; Pilar Aparicio-Martínez; Alberto-Jesus Perea-Moreno (Energies, 2022)
According to data provided by the International Energy Agency, buildings consume more than one-third of the energy produced globally and represent a major source of carbon dioxide-related emissions [...]